2016
DOI: 10.1002/jbio.201500315
|View full text |Cite
|
Sign up to set email alerts
|

SPR-based plastic optical fibre biosensor for the detection of C-reactive protein in serum

Abstract: A plastic optical fibre biosensor based on surface plasmon resonance for the detection of C-reactive protein (CRP) in serum is proposed. The biosensor was integrated into a home-made thermo-stabilized microfluidic system that allows avoiding any thermal and/or mechanical fluctuation and maintaining the best stable conditions during the measurements. A working range of 0.006-70 mg L and a limit of detection of 0.009 mg L were achieved. These results are among the best compared to other SPR-based biosensors for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 42 publications
1
39
0
Order By: Relevance
“…Over the past years, a FO-SPR biosensor was developed as a cost-effective and easy-to-use alternative for the more expensive and complex SPR systems [ 17 ], such as the well-known commercially available Biacore instrument (GE Healthcare, Uppsala, Sweden). The FO-SPR biosensor makes use of multimode optical fibers that facilitate SPR generation and enable implementation of bioassays [ 18 , 19 , 20 ]. As has already been demonstrated by our group, the FO-SPR biosensor developed in-house has the unique capacity to quantify a variety of different molecules, ranging from proteins and nucleic acids to small molecules not only in the buffer but also in the complex sample matrices, such as whole blood, serum, plasma or milk [ 14 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, a FO-SPR biosensor was developed as a cost-effective and easy-to-use alternative for the more expensive and complex SPR systems [ 17 ], such as the well-known commercially available Biacore instrument (GE Healthcare, Uppsala, Sweden). The FO-SPR biosensor makes use of multimode optical fibers that facilitate SPR generation and enable implementation of bioassays [ 18 , 19 , 20 ]. As has already been demonstrated by our group, the FO-SPR biosensor developed in-house has the unique capacity to quantify a variety of different molecules, ranging from proteins and nucleic acids to small molecules not only in the buffer but also in the complex sample matrices, such as whole blood, serum, plasma or milk [ 14 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the important measurand is represented by the surface RI changes induced by the interactions between the immobilized captures (AChE) and the target analytes (OP pesticide) along the functionalized surface, and not by the bulk RI changes related to the refractive index of the solution pumped inside the flow cell [39]. Therefore, the signal value after this washing step is considered as the real shift related to each MPT concentration.…”
Section: <Fig 7>mentioning
confidence: 99%
“…the measurement achieved with PBS right before applying pesticide [39,41]. From the calibration curve of Fig.…”
Section: <Fig 7>mentioning
confidence: 99%
“…During the performance analysis we choose RI from 1.33 to 1.43. This is because the RI of biochemical interactions goes from 1.33 to 1.35 however the range 1.33 to 1.43 is considered based on practical bio-chemical and chemical sensing [60,61]. It is observed that the resonance peak shift increases with the increase of analyte RI resulting in high sensitivity for larger RI.…”
Section: Investigation Of Sensor Performance By Optimizing Different mentioning
confidence: 99%